Child Marriage from a Gender Equality Perspective - Paridah Napilah; M. Yusuf Wibisono (Jurnal Iman dan Spiritualitas, 2026)
This article examines the practice of child marriage in Indonesia from a gender equality perspective by exploring the causal factors, socio-cultural constructions, and implications for women's health, education, and position within the social structure. Data from the Central Statistics Agency (BPS) and UNICEF show that the prevalence of child marriage remains high and its decline is very slow, indicating strong cultural roots, economic inequality, and unequal access to education. An international literature review confirms that low education, family economic pressure, and established social norms are the main determinants of this practice. From a health perspective, early pregnancy increases the risk of serious complications for both mother and baby and contributes to an intergenerational cycle of poverty. Gender analysis shows that child marriage reinforces unequal power relations between men and women, while limiting the space for identity development, social participation, and life opportunities for girls. From an Islamic perspective, the principles of gender equality and justice are guaranteed through the values of maqasid al-shari'ah, but their implementation is often hampered by biased social interpretations. This article emphasizes that the issue of child marriage cannot be separated from the structure of gender inequality and requires holistic interventions based on law, social, cultural, and theology to encourage sustainable change.